Livestock, community and environment - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
For the latest on veterinary medicine and education, livestock / environment interactions, peri- urban livestock, transboundary epizootic diseases and public health, you need to attend the international conference of the Association of Institutions...